Conversion of Cellobiose to Formic Acid as a Biomass‐Derived Renewable Hydrogen Source Using Solid Base Catalysts - Ikuto Yoshiki; Prof. Atsushi Takagaki; Dr. Jun Tae Song; Prof. Motonori Watanabe; Prof. Tatsumi Ishihara (ChemistryOpen)
Abstract Formic acid is considered a promising hydrogen carrier. Biomass‐derived formic acid can be obtained by oxidative decomposition of sugars. This study explored the production of formic acid from cellobiose, a disaccharide consisting of d‐glucose linked by β‐glycosidic bonds using heterogeneous catalysts under mild reaction conditions. The use of alkaline earth metal oxide solid base catalysts like CaO and MgO in the presence of hydrogen peroxide could afford formic acid from cellobiose at 343 K. While CaO gave 14 % yield of formic acid, the oxide itself was converted to a harmful metal peroxide, CaO2 after the reaction. In contrast, MgO could produce formic acid without the formation of the metal peroxide. The difficulty in selectively synthesizing formic acid from cellobiose using these solid base catalysts was due to the poor conversion of cellobiose to glucose. Using a combination of solid acid and base catalysts, a high formic acid yield of 33 % was obtained under mild reaction conditions due to the quantitative hydrolysis of cellobiose to glucose by a solid acid followed by the selective decomposition of glucose to formic acid by a solid base.